Editor’s note - Editorial, Equipe (Faculdade de Filosofia e Ciências, 2020)
As was the case in the last two issues of Estudos Kantianos, published in January and July p. p., the present issue contains articles of a future Electronic Kantian Lexicon in Portuguese Language, an enterprise which began in mid-2015 and congregates several Brazilian and Portuguese, but also German, Argentinian, Spanish, Italian and North-American collaborators.